The Context and Process of Theory Development: The Story of Ambiguous Loss. Issue 3 (September 2016) - Boss, Pauline
Abstract: This is the story of how the theory of ambiguous loss was born—the context of time and space in which it developed; the misunderstandings, clarifications, and corrections; and now, the theory's cultural updates. From an early interest in family stress theory, I coined the term ambiguous loss to name a previously unidentified stressor common to families everywhere. Discovering this phenomenon and developing the theory has been a lifelong process, but with a new generation of scholars, the theory continues to build and improve. This narrative is my tribute to a new generation of scholars, many of whom are testing the theory and broadening its application across cultures, disciplines, and types of ambiguous loss. May this account also stimulate the building of other useful theories of the middle range that include, without bias, the broad diversity of families today.